Rękopiśmienne wierszowane litteraria od średniowiecza do końca XVIII wieku w zbiorach benedyktynek sandomierskich. Część pierwsza: pieśni z kancjonału L 1642 - Trościński, Grzegorz (Tematy i Konteksty, 2014)
The object of interest is a description of manuscript L 1642 which belongs to the Diocesan Library in Sandomierz. This manuscript is a Hymnal, which was written in 1721 and it belonged to the Benedictine Sisters in Sandomierz. The material includes medieval European and Polish 16th and 17th century liturgical and paraliturgical songs. The texts in the manuscript are written in Latin and Polish. The Hymnal contains carols, the Advent, Easter and Passion songs among others; there are 77 works in total and only one has no musical notes (its text is written at the end of the manuscript). Most works are known and correspond with the content of other hymnals, e.g. the ones that belonged to the Benedictine Sisters in Staniątki, the Carmelite Sisters in Kraków, and the Clarisse Sisters in Gniezno. There are also some songs in Walenty Bartoszewski’s ("Parthenomelica albo Pienia nabożne o Pannie Najświętszej", 1613) and Stanisław Serafin Jagodyński’s works ("Pieśni katolickie nowo reformowane", 1638). The Hymnal is compiled by Anna Stogniewówna or, according to Magdalena Walter-Mazur, by Zofia Bratysiewiczówna. The manuscript is an interesting source of the known literary and musical culture of the Benedictine Sisters in Sandomierz. It also shows the popularity of these religious works. The Hymnal also contains some unknown versions of songs.